2017
DOI: 10.1088/1361-6382/aa9a11
|View full text |Cite
|
Sign up to set email alerts
|

Visible and dark matter profiles in a non-minimally coupled model

Abstract: A previous work found that a nonminimally coupled theory of gravity can, under appropriate conditions, give rise to an additional contribution to the field equations interpreted as dark matter [1]: in particular, the density of this dark matter component was found to scale as a power of the density of visible matter. However, no explicit solution for the modified field equations was provided, so that a direct computation of the specific density profile followed by visible matter is missing.This question is now… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…While this constraint falls short of the ones previously obtained from the black-body spectrum of the CMB, |n| few × 10 −6 , or from BBN, −0.002 < n < 0.003 [12], the present results are complementary as they more directly constrain the value of n at much smaller redshifts. Note that this rules out NMC models designed to mimic dark matter, as these would require a power-law with exponent in the range −1 ≤ n ≤ −1/7 in order to explain the observed galactic rotation curves [17,20], in accordance with previous results [12].…”
Section: A Power Lawsupporting
confidence: 84%
See 1 more Smart Citation
“…While this constraint falls short of the ones previously obtained from the black-body spectrum of the CMB, |n| few × 10 −6 , or from BBN, −0.002 < n < 0.003 [12], the present results are complementary as they more directly constrain the value of n at much smaller redshifts. Note that this rules out NMC models designed to mimic dark matter, as these would require a power-law with exponent in the range −1 ≤ n ≤ −1/7 in order to explain the observed galactic rotation curves [17,20], in accordance with previous results [12].…”
Section: A Power Lawsupporting
confidence: 84%
“…These changes depend on the Lagrangian of the matter fields which appears explicitly in the equations of motion and, therefore, the use of the correct Lagrangian is crucial in order to be able to derive useful constraints on NMC gravity. In previous work L m = −ρ or L m = p have been suggested as the on-shell Lagrangian of a perfect fluid with proper energy density ρ and pressure p [16][17][18][19][20]. However, the correct on-shell Lagrangian for a fluid composed of classical particles of fixed rest mass and structure has been shown to be given by the trace of the energy-momentum tensor of the fluid L m = T [11,21].…”
Section: Introductionmentioning
confidence: 99%
“…combining Eqs. (14), (15) and (16) one obtains that that the baryon-to-photon ratio η between BBN (at a redshift z BBN ∼ 10 9 ) and photon decoupling (at a redshift z CM B ∼ 10 3 ) evolves as…”
Section: Big-bang Nucleosynthesismentioning
confidence: 95%
“…The predictions of NMC theories are crucially dependent on the Lagrangian of the matter fields, and it is therefore imperative that the matter fields are appropriately described. In previous work L m = −ρ or L m = p have been suggested as the on-shell Lagrangian of a perfect fluid with proper energy density ρ and pressure p [13][14][15][16][17]. However, it has recently been shown that the correct on-shell Lagrangian for a fluid composed of solitonic particles of fixed rest mass and structure is given by the trace of the energy-momentum tensor of the fluid [11,18].…”
Section: Introductionmentioning
confidence: 99%